Effects of phosphate fertilization on growth and yield of irrigated sesame in semi-arid regions (Acta Scientiarum. Agronomy, 2025)
Exploring the effects of phosphorus on sesame development and yield in semi-arid environments is crucial for refining agronomic practices and enhancing crop productivity. This research evaluated the response of sesame cultivars to varying phosphorus levels under irrigation in a semi-arid setting. Conducted at the Experimental Farm of the Federal Rural University of the Semi-Arid, two experiments ran from August to November in 2021 and 2022. A randomized block design with subdivided plots and four replicates was employed. Treatments consisted of five phosphorus doses (0, 60, 120, 180, and 240 kg ha-1 of P2O5) applied to main plots, while four sesame cultivars (CNPA G2, CNPA G3, CNPA G4, and BRS Seda) were assigned to subplots. Variables such as plant height, stem diameter, leaf count, capsule count, above-ground dry matter, thousand-seed weight, and seed yield were assessed. Phosphorus application significantly enhanced plant growth, which correlated positively with seed yield. Optimal phosphorus doses for peak seed yield in the first harvest were 170, 184, 167, and 152 kg ha-1 of P2O5 for cultivars CNPA G2, CNPA G3, CNPA G4, and BRS Seda, respectively. The second harvest showed maximum yields at doses of 149, 137, 125, and 164 kg ha-1 of P2O5. Notably, the second harvest yielded better plant development. Response to phosphorus varied among cultivars, with CNPA G3 and CNPA G4 showing the highest growth and productivity.